Corporate Social Responsibility, Financial Distress, Dan Siklus Hidup Perusahaan - Elsa Fitri Utami; Annisaa Rahman; Rayna Kartika (Ekonomis: Journal of Economics and Business, 2021)
The purpose of this study is to prove that corporate social responsibility has a negative effect on financial distress and test corporate social responsibility against financial distress in different life cycle stages. Corporate social responsibility in this study measured using Global Reporting Iniative (GRI)-G4. Financial distress in this study measured using Altman’s Z-score model. This study classifies the life cycle of companies using cash flow pattern that includes phase start-up, growth, mature, and decline. The population in this study were all companies listed on the Indonesia Stock Exchange from 2014 - 2018. The sample of this study was 269 companies. Data was analyzed using logistic regression methods. The results showed that corporate social responsibility disclosure has a negative effect on financial distress. There is no evidence to support that at the start-up stage, CSR has a positive effect on financial distress. In the life cycle of the growth and mature stages, CSR has a negative and significant effect on financial distress. There is no evidence to support that at the stage of decline, CSR has a negative effect on financial distress.